Evaluating the Effectiveness of Keyword, Phrase, Boolean Operator [AND] in Bibliographic Data Access and Retrieval for the Subject Chemistry - Saravanan, T (Library philosophy and practice, 2020)
The present study focuses on information search and retrieval of the bibliographical data related to the key terms that fall in the subject chemistry. The search techniques include simple keywords, phrase terms and Boolean operator "AND". Further, study encompasses the Lancaster's 2 x 2 Table matrix to trace the recall (R) and precision (P) ratio for the obtained records that are retrieved from the bibliographic database using the same search techniques. To fulfil the aims of the present study, a bibliographic database which contains the doctoral theses belonging to various subjects submitted to Annamalai University has been vouched. The database consists of 1641 records and was built using Unesco's Java CDS/ISIS (Jean-Claude Dauphin, 2016). The queries used in this study are acid, correlation, kinetics, oxidation, kinetics of oxidation, (acid AND chemistry), (kinetics AND oxidation), and (kinetics AND oxidation AND correlation).